2020
DOI: 10.1111/jhn.12831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight management nutrition interventions on dietary outcomes in children and adolescents with overweight or obesity: a systematic review with meta‐analysis

Abstract: Impact of weight management nutrition interventions on dietary outcomes in children and adolescents with overweight or obesity: a systematic review with meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 135 publications
0
41
0
2
Order By: Relevance
“…For instance, children and adolescents usually consume fewer FV and other fiber sources [85,86] than adults. Notably, evidence from systematic reviews [87,88] showed that children and adolescents had lower adherence to national FBDGs, and that families play an important role in influencing their eating behaviors [89,90]. Thus, family aspects of eating behavior might be included as key messages on public health initiatives and other resources for the population.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, children and adolescents usually consume fewer FV and other fiber sources [85,86] than adults. Notably, evidence from systematic reviews [87,88] showed that children and adolescents had lower adherence to national FBDGs, and that families play an important role in influencing their eating behaviors [89,90]. Thus, family aspects of eating behavior might be included as key messages on public health initiatives and other resources for the population.…”
Section: Discussionmentioning
confidence: 99%
“…The high rates of overweight and obesity continue to be an important public health concern among adolescents. 1 In Canada, 24.5% of adolescents aged between 12 and 17 report being overweight or obese. 2 Prior research has well-established that overweight and obesity are negatively associated with adolescents’ health and well-being.…”
Section: Purposementioning
confidence: 99%
“…Obesity is classified as a chronic disease and it is of great importance that children receive treatment [2,3]. While obesity treatment for young children is rare, treatment at an early age seems to have the most beneficial effect [4,5], and interventions have shown promising results with clinically significant weight loss [4] and a lower energy intake up to 1 year after starting treatment [6].…”
Section: Introductionmentioning
confidence: 99%